Aquatic ecological knowledge systems as linguistic and cultural resources in philology education - Xudoyberdiyeva, Zumrat; Abdurahimova, Manzura; Tangirov, Ruziboy; Nazarova, Sevarakhon; Shukrullayeva, Durdona; Abdumalikova, Dilfuza; Khushvaktova, Khusnobod (International Journal of Aquatic Research and Environmental Studies, 2026)
The Aquatic Ecological Knowledge Systems (AEKS) are a lucrative collection of linguistic and cultural knowledge that are inculcated in indigenous and local communities, but it is not used in the education of philology. This paper takes the qualitative research design based on ethnographic-textual research to explore how AEKS would facilitate the improvement of semantic analysis, etymological inquiry, and discourse interpretation within culturally-focused learning setting. The study was carried out in a 12 weeks academic span with 42 students and 3 instructors in selected courses in philology. The information was gathered with the help of textual analysis of the literary resources on aquatic topics, observations in the classroom, curriculum analysis, and semi-structured interviews. The results show that the inclusion of AEKS in philological teaching such as the enhancement of ecological lexicon, metaphorical interpretation, and contextualization of culture. The learners showed more interest in indigenous words and ecological stories, which resulted in more sophisticated and context-aware textual interpretation. The paper indicates that AEKS are dynamic linguistic and cultural archives that facilitate interdisciplinary learning and eco-cultural literacy. It sums up that ecological knowledge should be added to the philology curriculum in order to increase the level of interpretation and achieve culturally responsive language education.
Keywords: Aquatic ecological knowledge systems; Philology education; Indigenous linguistic heritage; Eco-Linguistics; Cultural semantics; Traditional ecological knowledge; Interdisciplinary language pedagogy